Kalman equalizer performance in GPS System - F. Agus Priambodo (University of Merdeka Malang, 2005)
Today, many GPS systems operate in distorted areas, so the need for an equalizer is absolute. The Zero Forcing Equalizer type which is controlled by a data-based channel estimator is the most widely used type of equalizer. The Kalman equalizer was tried to improve the performance of the Zero Forcing equalizer, in terms of Mean Squared Error (MSE). The channel is modeled as a multipath fading channel according to the Jake channel, arranged in the form of a tapped delay line based on the measured power delay profile. The data-based channel estimator model uses a training sequence that is sent to each frame, with a GSM frame structure. The equalizer is modeled as a zero-forcing equalizer controlled by a channel estimator and a direct form Kalman equalizer.